The Social Objectives of Economic Development - Kaplansky, Kalmen (Relations industrielles / Industrial Relations, 1969)
The author summarizes the l.L.O.'s technical co-operation activities and their evolution from the early 1930's until the present time by highlighting some of the main topics and making a few supplementary observations.